As escolas diferenciadas dos Índios Tapebas - Aires, Jouberth Max Maranhão Piorsky (2005)
Since the end of the 1980's, the tapebas Indians (Caucaia- CE) have been postulating and implementing in practice experiences of school organisation in their "communities". Emphasis is given to the fact that schools amongst the indigenous people are a result of the visibility that this population has achieved locally and is a deepening of what their leaders call the "struggle". The "struggle" basically refers to the political deadlock between the Tapeba and society regarding the guarantee of social rights, which initially centred on land disputes. Lately, with the growing visibility of this population, schools and other social requirements have been added to the political list of demands, due to new possibilities for the recognition of their rights At first, schools were desirable in the "communities" to achieve literacy. By the beginning of the 1990's; leaders and teachers had added arguments that emphasised the inclusion of cultural differences in the curricula, calling the school " The Differentiated School of Tapeba". This revindication is interposed by the intervention of government agencies and non-governmental agencies that have postulated a repertoire of themes about the schooling of Indians. Such themes are guided by the new paths taken by the national policy for Indians' school education, which despite its advances, is adopted unquestioned by experts, who also use knowledge and representations about the cultural dynamics and spatial location of indigenous people that are always distant from the Tapeba's reality. In this context, the agencies' position has impelled teachers and leaders to act strategically to guarantee maintenance and meet the educational demands made by the Indians, who call for a "different" and "bilingual" school. It is argued that the theme of difference has various meanings for teachers and indigenous leaders, as this is the territory of the dualistic reproduction of the western idea of difference which uses a "common anthropological sense"(a), as well as a political strategy of implanting important themes for the "struggle" in the children (b) and, also, an instrument to guarantee visibility before the agencies (c). The themes which emerge from the struggle are reference points for the teachers, despite of the fact that the school is marked by the traditional, non-indigenous pedagogical routine and by the reproduction of the stereotyped image of the Indian. The indigenous Tapeba school presents a dual image in its conquest of universal knowledge and cultural differences, a strategy for joining and leaving modernity, at the same time.